Impact Of Natural Disaster On Local Tax Revenue - Anugerah, Bima Satria; Wijaya, Suparna (WIM Solusi Prima, 2024)
Poverty is one of the problems that always become main concern in Indonesia, the problem of poverty is worsen when economic shocks occur, one of which caused by natural disasters, these two things adding the burden on the government, especially at the regional level both in the context of fiscal management and countermeasures. By using panel data from 34 provinces in Indonesia, this study aims to find the effect of natural disasters and poverty rate on regional tax revenues at provincial level with foreign direct investment (FDI) as a moderating variable. The results of the regression shows that natural disasters and the poverty rate have positive effects on local tax revenues, but these two variables become negatively affected when moderated by FDI so that moderation weakens the effect of the two independent variables, the FDI variable itself when tested as an independent variable has positive effects on local tax revenues. This research is expected to assist local governments in formulating fiscal policy in the event of a post-disaster economic shock and its countermeasures as well as poverty alleviation efforts when the economy is running normally.